Phosphorylation of Gata1 at serine residues 72, 142, and 310 is not essential for hematopoiesis in vivo - Rooke, Heather M. (The American Society of Hematology, 2006)
Phosphorylation of transcription factors is important in posttranslational control of protein function. The indispensable zinc-finger transcription factor, Gata1, is phosphorylated constitutively at 6 serine residues (26, 49, 72, 142, 178, 187), and at a seventh (310) following induction of erythroid differentiation. However, the biologic consequences of phosphorylation with respect to function are unclear. To address this issue, we generated mice with serine-to-alanine mutations at the inducibly phosphorylated serine 310 alone or at conserved serine residues 72, 142, and 310 together. The peripheral blood parameters of the mice were normal, as was their response to acute erythropoietic stress. Analysis of hematopoietic progenitor populations during ontogeny and into adulthood showed a moderate decrease in erythroid burst-forming unit (BFU-E) and erythroid colony-forming unit (CFU-E) numbers only in the adult bone marrow of the triple mutant. Yet, later stage erythropoiesis was not perturbed. This suggests that any molecular consequences associated with loss of phosphorylation at residues 72, 142, and 310 can be compensated for in the in vivo environment.